Case report: Two cases of leptomeningeal metastases in patients with metastatic urothelial carcinoma treated with enfortumab vedotin - Fishbein, Francine; Nappi, Lucia; Mortazavi, Behnoush; Eigl, Bernhard (Frontiers in Oncology, 2024)
BackgroundLeptomeningeal carcinomatosis is an exceptionally rare pattern of metastases in genitourinary cancer, described in less than 0.1% of cases. We report two cases of patients with metastatic urothelial cancer who initially responded to enfortumab vedotin (EV) before developing leptomeningeal metastases.Case presentationCase 1: A 55 year-old man was diagnosed with metastatic urothelial carcinoma. He was initially treated with cisplatin/gemcitabine chemotherapy, followed by second-line pembrolizumab, with progression on both of these regimens. He was started on EV therapy and had a sustained partial response. After 12 cycles of treatment, he developed neurologic symptoms with imaging showing extensive leptomeningeal metastases. A lumbar puncture was performed with cytology positive for metastatic carcinoma. Case 2: A 63 year-old man was diagnosed with metastatic urothelial carcinoma. He received 6 cycles of platinum/gemcitabine chemotherapy followed by avelumab maintenance, after which he developed radiographic progression. He was started on EV therapy and developed a complete radiographic response. After 13 cycles of treatment, he developed neurologic symptoms and imaging revealed extensive leptomeningeal disease. Cytology confirmed metastatic urothelial carcinoma.ConclusionThis uncommon pattern of spread observed in two patients treated with EV in short succession represents a potentially significant and novel pattern of progression within this population.